Design methodology of urban air mobility for noise mitigation at conceptual design stage - Kim, H.; Lee, D.; Seo, J.; Hong, Y.; Yee, K. (My University, 2022)
This article proposes a design methodology for UAM vehicles for noise mitigation at a conceptual design stage. A rotor analysis module for accurate noise prediction and a noise prediction module for a conceptual design stage are constructed. The rotor analysis module is developed for accurately predicting aerodynamic force distribution around rotor blades, thus enabling accurate noise prediction. This module consists of rotor analysis using BEMT or BET methods and CAMRAD II, and these methods exchange force distribution data, which is iterated in the module until aerodynamic force distribution by each method converges. The noise prediction module for a conceptual design stage uses compact loading assumption and dual compact loading assumption, therefore loading and thickness noise prediction are completed in a short time. The proposed design methodology is applied to a conceptual design of an eVTOL aircraft with the lift+cruise concept. Through the design optimization process, the necessity of considering noise impact at the conceptual design stage is demonstrated.